A Corrosion Protection Technology for Large Marine Steel Structures
By adopting weather-resistant anticorrosion coatings and improved spraying processes on large marine steel structures, the problem of insufficient binding force of anticorrosion coatings in the marine environment is solved, and higher binding force and longer service life are achieved, while reducing marine biological adhesion.
Patent Information
- Application Number
- CN202410363614.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-03-28
- Publication Date
- 2025-04-01
AI Technical Summary
The marine environment has extremely serious corrosion to metals and concrete materials. The existing large marine steel structures have insufficient anticorrosion coatings, resulting in a short service life.
The anti-corrosion process of large marine steel structures is adopted, including pre-environmental preparation, surface treatment, spraying and post-treatment steps, and weather-resistant anti-corrosion coatings are used, which consist of water-based epoxy resin, modified water-based polyurethane, carbon nanotubes and natural anti-fouling materials. The adhesiveness and density of the coating are improved by modifying polymer network structure and hydrogen bonding.
It significantly improves the binding force and mechanical properties of the anticorrosion coating, extends the service life of the anticorrosion coating, effectively reduces the adhesion of marine organisms, and protects large marine steel structures.
Smart Images

Figure BDA0004763493360000061 
Figure BDA0004763493360000071
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of steel structure anti-corrosion materials, and more specifically, to an anti-corrosion process for large marine steel structures. Background Art
[0002] In recent years, with the advancement of marine development, marine projects such as cross-sea bridges, offshore survey platforms, oil production platforms, port terminals, etc. are also being gradually carried out. However, since seawater contains various salts, chloride ions, sulfides and other corrosive substances, the marine environment is extremely corrosive to metal and concrete materials. Therefore, in the fields of marine engineering, marine equipment and ships, the importance of marine corrosion protection is becoming more and more prominent.
[0003] At present, anti-corrosion coatings are mainly used to protect large marine steel structures. The bonding strength between the anti-corrosion coating and the metal interface is a key factor affecting the service life of the anti-corrosion coating. Therefore, there is an urgent need for a marine anti-corrosion coating and anti-corrosion process with excellent bonding strength. Summary of the invention
[0004] In order to improve the bonding strength of marine anti-corrosion coatings, the present application provides an anti-corrosion process for large marine steel structures.
[0005] The present application provides an anti-corrosion process for large marine steel structures, which adopts the following technical solutions: An anti-corrosion process for large marine steel structures comprises the following steps: Preliminary environmental preparation: control the surface temperature of the coated metal to be 3°C higher than the dew point temperature, and the air humidity to be less than 85%; Preliminary surface treatment: use sandpaper to remove debris from the surface to be sprayed, and then use a brush to pre-coat the parts that are difficult to spray, such as the structure edge, welding hole and weld; One spraying: Firstly, test the spray gun, keep the spray gun vertical to the surface of the workpiece, and spray at a distance of 300-500mm; then spray with an overlap width of 50%. If dripping occurs during spraying, brush it flat immediately with a brush; the paint just sprayed should not be removed from the spray room before it is dry; Post-processing: inspect the coating surface and repair abnormal traces such as convex spots, overspray, roughness, pinholes, depressions, and coating leaks; Second treatment: Use sandpaper to remove pollutants on the surface of the first coating, and then perform gun test, spraying and repair operations; In the first spraying and second treatment, weather-resistant anti-corrosion coating is used for spraying, and the weather-resistant anti-corrosion coating includes the following raw materials in parts by weight: 90-110 parts of water-based epoxy resin emulsion, 10-16 parts of modified water-based polyurethane, 5-10 parts of water-based epoxy curing agent, 10-20 parts of carbon nanotubes, 3-8 parts of film-forming aid, 0.2-0.8 parts of defoaming agent, 0.3-0.9 parts of wetting agent, 0.6-1.2 parts of dispersant, 0.6-1.2 parts of leveling agent and 10-16 parts of water.
[0006] Epoxy resin has excellent chemical corrosion resistance, excellent adhesion to a variety of substrates, and the coating formed by its curing is dense, rigid, and has good heat and wear resistance. However, epoxy resin coating has the disadvantage of low adhesion. However, when epoxy resin is used in combination with polyurethane, the polyurethane segments and epoxy resin segments will penetrate each other, thus forming an interpenetrating polymer network structure, thereby improving the adhesion of the coating.
[0007] Carbon nanotubes can form strong hydrogen bonds with the coating, enhancing the density and resistance to ion permeability of the coating. At the same time, they can also improve the rheological properties of the coating, increase the adhesion and hardness of the coating, thereby increasing the bonding strength of the marine anti-corrosion coating itself and effectively extending the service life of the anti-corrosion coating.
[0008] Preferably, in the first post-treatment and the second treatment, the repair operation is: sanding with sandpaper within 50 mm around the abnormal area to make the coating surface rough, and then performing local spray repair when the single abnormal trace area is no larger than 1 square foot and the sum of the damaged area does not exceed 10% of the total area, otherwise the whole is boraxed and re-painted.
[0009] Preferably, for paint damage that exposes the base material, the repair operation is: clean the damaged area to remove pollutants, then protect the intact paint surface with rubber, and tie it tightly with wire or tape, then apply borax to the damaged area until SA2 1 / 2 , then grind the paint in the junction area to remove the fine crack coating; then sand the edges of the damaged area and the intact area to create an overlapping slope, the original coating in the overlapping area should be sanded to reveal a fresh coating surface, and finally clean the surface and paint.
[0010] When the above-mentioned spraying process and repair process are adopted, the prepared anti-corrosion coating will be denser and more complete, and the bonding interface between the coating and the substrate will be tighter, effectively improving the bonding strength and mechanical properties of the anti-corrosion coating.
[0011] Preferably, the modified waterborne polyurethane contains natural antifouling materials, and the natural antifouling materials are extracts of one or more of Beibu Gulf flower corals, seaweed giant algae and marine streptomyces.
[0012] The attachment of marine organisms in the ocean is also extremely harmful to large marine steel structures. Therefore, in order to reduce the impact of marine organisms on large marine steel structures, materials such as zinc ions, copper ions, and tin ions can usually be added to the marine anti-corrosion coating to inhibit the attachment of marine organisms through the interference effect of metal ions. However, when the metal ion content is too high, the metal ions will be enriched in the marine organisms, thereby affecting the entire ecological balance and causing serious harm to the marine environment.
[0013] The Beibu Gulf gorgonian coral, seaweed eel and marine streptomyces all contain natural substances that repel marine organisms. The three have very low impacts on the marine ecological environment. Their anti-marine biological mechanism lies in the fact that the Beibu Gulf gorgonian coral extract contains a large number of macrolide compounds and diterpenoid compounds, and the above compounds have excellent anti-fouling activity against barnacle larvae. The seaweed eel extract contains P-cinnamic acid sulfate, which has an inhibitory effect on the attachment of marine bacteria and barnacles. The marine streptomyces extract contains butenolide, which has a degrading effect on the adhesion protein polymer formed by biological adhesion, thereby reducing the strength of biological adhesion and naturally detaching from large marine steel structures under the action of environmental external forces.
[0014] Preferably, the natural antifouling material is a mixed extract of Beibu Gulf gorgonian coral, seaweed eel and marine streptomyces, and the mass ratio of Beibu Gulf gorgonian coral, seaweed eel and marine streptomyces is (3-5): (1-3): (2-4).
[0015] Compared with the use of extracts of Beibu Gulf gorgonian coral, seaweed eel and marine streptomyces alone, the mixed extracts of Beibu Gulf gorgonian coral, seaweed eel and marine streptomyces can inhibit marine organisms in multiple ways, thereby forming a synergistic effect and further reducing the attachment of marine organisms. Among them, when the mass ratio of Beibu Gulf gorgonian coral, seaweed eel and marine streptomyces is (3-5): (1-3): (2-4), the prepared weather-resistant anti-corrosion coating will have a better anti-marine biological effect.
[0016] Preferably, the modified waterborne polyurethane contains attapulgite, and the natural antifouling material is loaded on the attapulgite.
[0017] Although natural antifouling materials have excellent marine antifouling effects, the effectiveness of the above natural antifouling materials is relatively short, and under the scouring of seawater, the natural antifouling materials in weather-resistant anticorrosion coatings are easily precipitated and detached. Attapulgite has a large number of pore structures, which can effectively adsorb natural antifouling materials, thereby inhibiting the detachment of natural antifouling materials and indirectly improving the anti-marine biological attachment effect of weather-resistant anticorrosion coatings.
[0018] Preferably, the modified waterborne polyurethane comprises the following raw materials in molar parts: 1-3 parts of 1-thioglycerol, 5-10 parts of butyl acrylate, 5-10 parts of N-vinyl pyrrolidone, 0.1-0.2 parts of 2,2-azobisisobutyronitrile, 10-20 parts of isophorone diisocyanate, 2-8 parts of double-terminal hydroxypropyl silicone oil, 0.5-1.5 parts of polytetrahydrofuran, 0.4-0.8 parts of dibutyltin dilaurate, 6-10 parts of 1,4-butanediol, 1-3 parts of triethanolamine, 3-5 parts of attapulgite and 2-4 parts of natural antifouling materials.
[0019] Preferably, the preparation method of the modified waterborne polyurethane comprises the following steps: S1, dissolving 1-thioglycerol, butyl acrylate, N-vinyl pyrrolidone and 2,2-azobisisobutyronitrile in tetrahydrofuran, and then reacting at 70° C. for 12 h under a nitrogen atmosphere, then removing the solvent, and precipitating with petroleum ether, and finally drying the precipitate to obtain a hydrophilic polymer; S2, dissolving isophorone diisocyanate, double-terminated hydroxypropyl silicone oil, polytetrahydrofuran and dibutyltin dilaurate in tetrahydrofuran, and then reacting at 70°C for 3h, then adding 1,4-butanediol and a hydrophilic polymer, heating to 80°C for 3h, and then adding triethanolamine to continue the reaction for 0.5h, and finally obtaining an amphiphilic polyurethane; S3, soaking the attapulgite in natural antifouling materials, then drying it naturally, and then mixing it with amphiphilic polyurethane to obtain modified waterborne polyurethane.
[0020] The amphiphilic polyurethane contains hydrophilic segments and hydrophobic segments, wherein the hydrophilic segments are conducive to inhibiting the formation of adhesion proteins, and the hydrophobic segments are conducive to reducing the polarity and hydrogen bonding between the silted bioadhesive and the matrix, thereby obtaining an excellent anti-marine biological adhesion effect. In addition, the silicon-oxygen bonds in the amphiphilic polyurethane can also be connected with the hydroxide on the attapulgite, thereby further inhibiting the release of natural antifouling materials and indirectly improving the anti-marine biological adhesion effect of the weather-resistant anticorrosion coating.
[0021] Preferably, the preparation method of the weather-resistant anticorrosive coating comprises the following steps: Step 1: Mixing the waterborne epoxy resin emulsion and the modified waterborne polyurethane, and then sequentially adding a defoamer, a wetting agent, a dispersant, a leveling agent and water to obtain a coating base material; Step 2: adding carbon nanotubes to the coating base material and continuing to mix to obtain a weather-resistant and anti-corrosion coating body; Step 3: Mix the water-based epoxy curing agent with the weather-resistant anti-corrosion coating to finally obtain the weather-resistant anti-corrosion coating.
[0022] In summary, this application has the following beneficial effects: 1. When epoxy resin and polyurethane are used in combination, the polyurethane segments and epoxy resin segments will penetrate each other, thus forming an interpenetrating polymer network structure, thereby improving the adhesion of the coating film.
[0023] 2. Carbon nanotubes can form strong hydrogen bonds with the coating, enhancing the density and resistance to ion permeability of the coating. At the same time, they can also improve the rheology of the coating, increase the adhesion and hardness of the coating, and thus increase the bonding strength of the marine anti-corrosion coating itself, effectively extending the service life of the anti-corrosion coating.
[0024] 3. The Beibu Gulf gorgonians, seaweed eelgrass and marine streptomyces all contain natural substances that repel marine organisms. The three have extremely low impacts on the marine ecological environment. Compared with the use of extracts of the Beibu Gulf gorgonians, seaweed eelgrass and marine streptomyces alone, the mixed extracts of the Beibu Gulf gorgonians, seaweed eelgrass and marine streptomyces can inhibit marine organisms in multiple ways, thus forming a synergistic effect and further reducing the attachment of marine organisms.
[0025] 4. The amphiphilic polyurethane contains hydrophilic segments and hydrophobic segments, wherein the hydrophilic segments are conducive to inhibiting the formation of adhesion proteins, and the hydrophobic segments are conducive to reducing the polarity and hydrogen bonding between the silted bioadhesive and the matrix, thereby obtaining an excellent anti-marine biological adhesion effect. In addition, the silicon-oxygen bonds in the amphiphilic polyurethane can also be connected with the hydroxide on the attapulgite, thereby further inhibiting the release of natural antifouling materials and indirectly improving the anti-marine biological adhesion effect of the weather-resistant anticorrosion coating. DETAILED DESCRIPTION
[0026] The present application is further described in detail below in conjunction with Examples 1-12 and Comparative Example 1.
[0027] raw material Waterborne epoxy resin emulsion Changyao Chemical CY-HR5; waterborne epoxy curing agent Meiyang Times WRH 6765; carbon nanotube Aladdin 308068-56-6; film-forming aid DPNB 29911-28-2; defoamer BYK-A530; wetting agent BYK-W996; dispersant STA-1110A; leveling agent ZY-318; Beibu Gulf flower coral Guangxi Xiayang Island; seaweed giant algae Shandong coast; marine streptomyces HS-B34; ethanol CAS: 64-17-5; dichloromethane CAS: 75-09-2; attapulgite CAS: 1337-76-4; 1-thioglycerol CAS: 96-2 7-5; butyl acrylate CAS: 141-32-2; N-vinyl pyrrolidone CAS: 88-12-0; 2,2-azobisisobutyronitrile CAS: 78-67-1; isophorone diisocyanate 4098-71-9; double-terminated hydroxypropyl silicone oil Hubei Shuai Yan Li Gao; polytetrahydrofuran CAS: 25190-06-1; 1,4-butanediol CAS: 110-63-4; triethanolamine CAS: 102-71-6. Example
[0028] Example 1 An anti-corrosion process for large marine steel structures comprises the following steps: Preliminary environmental preparation: control the surface temperature of the coated metal to be 3°C higher than the dew point temperature, and the air humidity to be less than 85%; Preliminary surface treatment: use sandpaper to remove debris from the surface to be sprayed, and then use a brush to pre-coat the parts that are difficult to spray, such as the structure edge, welding hole and weld; One spraying: Firstly, test the spray gun, keep the spray gun vertical to the surface of the workpiece, and the spraying distance is 400mm; then spraying operation, the overlap width is 50% during spraying, if there is sagging during spraying, immediately brush it flat with a brush; the paint just sprayed will not be removed from the spraying room before it is dry; Post-processing: inspect the coating surface and repair abnormal traces such as convex spots, overspray, roughness, pinholes, depressions, and coating leaks; Second treatment: Use sandpaper to remove pollutants on the surface of the first coating, and then perform test gun, spray and repair operations.
[0029] In the first post-treatment and the second treatment, the repair operation is: sandpaper is used to polish within 50mm around the abnormal area to make the coating surface rough, and then local spray repair is carried out when the single abnormal trace area is not larger than 1 square foot and the sum of the damaged area does not exceed 10% of the total area, otherwise the whole borax is applied and re-painted.
[0030] For paint damage that exposes the base material, the repair operation is as follows: clean the damaged area until there is no contaminant, then use rubber to protect the intact paint surface and tie it tightly with wire or tape, then apply borax to the damaged area until SA2 1 / 2 , then grind the paint in the junction area to remove the fine crack coating; then sand the edges of the damaged area and the intact area to create an overlapping slope, the original coating in the overlapping area should be sanded to reveal a fresh coating surface, and finally clean the surface and paint.
[0031] In the first spraying and second treatment, weather-resistant anti-corrosion coating is used for spraying. The weather-resistant anti-corrosion coating includes the following raw materials: 100g water-based epoxy resin emulsion, 13g modified water-based polyurethane, 8g water-based epoxy curing agent, 15g carbon nanotubes, 6g film-forming aid, 0.5g defoaming agent, 0.6g wetting agent, 0.9g dispersant, 0.9g leveling agent and 13g water.
[0032] The preparation method of the weather-resistant anticorrosive coating comprises the following steps: Step 1: Mixing the waterborne epoxy resin emulsion and the modified waterborne polyurethane, and then sequentially adding a defoamer, a wetting agent, a dispersant, a leveling agent and water to obtain a coating base material; Step 2: adding carbon nanotubes to the coating base material and continuing to mix to obtain a weather-resistant and anti-corrosion coating body; Step 3: Mix the water-based epoxy curing agent with the weather-resistant anti-corrosion coating to finally obtain the weather-resistant anti-corrosion coating.
[0033] The modified waterborne polyurethane comprises the following raw materials in molar amounts: 2 mol 1-thioglycerol, 7 mol butyl acrylate, 8 mol N-vinyl pyrrolidone, 0.15 mol 2,2-azobisisobutyronitrile, 15 mol isophorone diisocyanate, 5 mol double-terminal hydroxypropyl silicone oil, 1 mol polytetrahydrofuran, 0.6 mol dibutyltin dilaurate, 8 mol 1,4-butanediol, 2 mol triethanolamine, 4 mol attapulgite and 3 mol natural antifouling materials.
[0034] The natural anti-fouling material is a mixed extract of Beibu Gulf gorgonian coral, seaweed giant kelp and marine streptomyces. The extract is a 1:1 mixture of ethanol and dichloromethane. The mass ratio of Beibu Gulf gorgonian coral, seaweed giant kelp and marine streptomyces is 4:2:3.
[0035] The preparation method of modified waterborne polyurethane comprises the following steps: S1, dissolving 1-thioglycerol, butyl acrylate, N-vinyl pyrrolidone and 2,2-azobisisobutyronitrile in tetrahydrofuran, and then reacting at 70° C. for 12 h under a nitrogen atmosphere, then removing the solvent, and precipitating with petroleum ether, and finally drying the precipitate to obtain a hydrophilic polymer; S2, dissolving isophorone diisocyanate, double-terminated hydroxypropyl silicone oil, polytetrahydrofuran and dibutyltin dilaurate in tetrahydrofuran, and then reacting at 70°C for 3h, then adding 1,4-butanediol and a hydrophilic polymer, heating to 80°C for 3h, and then adding triethanolamine to continue the reaction for 0.5h, and finally obtaining an amphiphilic polyurethane; S3, soaking the attapulgite in natural antifouling materials, then drying it naturally, and then mixing it with amphiphilic polyurethane to obtain modified waterborne polyurethane.
[0036] The preparation method of the weather-resistant anticorrosive coating comprises the following steps: Step 1: Mixing the waterborne epoxy resin emulsion and the modified waterborne polyurethane, and then sequentially adding a defoamer, a wetting agent, a dispersant, a leveling agent and water to obtain a coating base material; Step 2: adding carbon nanotubes to the coating base material and continuing to mix to obtain a weather-resistant and anti-corrosion coating body; Step 3: Mix the water-based epoxy curing agent with the weather-resistant anti-corrosion coating to finally obtain the weather-resistant anti-corrosion coating.
[0037] Example 2-3 The difference from Example 1 is that the added amounts of the components of the weather resistant and anti-corrosion coating are different, as shown in Table 1.
[0038] Table 1 Addition amount of each component of the weather-resistant anticorrosive coating of Example 1-3 / g Example 1 Example 2 Example 3 Waterborne epoxy resin emulsion 100 110 90 Modified waterborne polyurethane 13 10 16 Waterborne epoxy curing agent 8 10 5 Carbon Nanotubes 15 10 20 Film-forming aids 6 8 3 Defoaming agent 0.5 0.8 0.2 Wetting Agents 0.6 0.9 0.3 Dispersants 0.9 0.6 1.2 Leveling agent 0.9 1.2 0.6 water 13 16 10 Embodiment 4-5 The difference from Example 1 is that the molar amounts of the components of the modified waterborne polyurethanes in Examples 4-5 are different, as shown in Table 2.
[0039] Table 2 Molar amounts of each component of modified waterborne polyurethane in Example 1 and Examples 4-5 / mol Embodiment 6-7 The difference from Example 1 is that the mass proportions of the components of the natural antifouling material are different, as shown in Table 3.
[0040] Table 3 Mass ratio of each component of natural antifouling material in Example 1, Example 6-7 Example 1 Example 6 Example 7 Tonkin Gulf Flower Gorgonian Coral 4 5 3 Seaweed Erythrophyllum 2 3 1 Streptomyces marineus 3 2 4 Example 8 The difference from Example 1 is that the natural antifouling material is only the extract of the Beibu Gulf gorgonian coral.
[0041] Example 9 The difference from Example 1 is that the natural antifouling material is only the extract of seaweed Zostera marina.
[0042] Example 10 The difference from Example 1 is that the natural antifouling material is only the extract of marine Streptomyces.
[0043] Embodiment 11 The difference from Example 1 is that attapulgite is no longer added to the modified waterborne polyurethane.
[0044] Example 12 The difference from Example 1 is that the modified water-based polyurethane is replaced by a natural anti-fouling material, and the natural anti-fouling material is a mixed extract of Beibu Gulf flower coral, seaweed giant kelp and marine streptomyces. The extract is a 1:1 mixture of ethanol and dichloromethane, and the mass ratio of Beibu Gulf flower coral, seaweed giant kelp and marine streptomyces is 4:2:3.
[0045] Comparative Example Comparative Example 1 The difference from Example 1 is that modified waterborne polyurethane and carbon nanotubes are no longer added to the weather-resistant and anti-corrosion coating.
[0046] Performance testing Detection Methods 1. Adhesion performance test Three samples were taken from Examples 1-3 and Comparative Example 1 respectively. After the paint was cured for 12 days, the bonding substrate was an iron plate. The samples were tested using ASTM D4541 "Paint Film Adhesion Pull-off Test". Finally, the bonding strength was obtained and the average value was taken. The test data is shown in Table 4.
[0047] Table 4 Adhesion performance test table of Examples 1-3 and Comparative Example 1 / MPa Adhesive strength / MPa Adhesive strength / MPa Example 1 16.83 Example 3 16.28 Example 2 16.32 Comparative Example 1 14.83 2. Anti-marine bioadhesion test One hundred samples were taken from Example 1 and Examples 4-12 respectively, and then all the samples were coated on iron plates and cured for 12 days. Then all the iron plates were immersed in seawater, and 30 barnacle larvae were cultured in the seawater for 120 hours. At the same time, the seawater was simulated to flow, and finally the proportion of barnacles attached to each group of example samples was recorded, as shown in Table 5.
[0048] Table 5 Anti-marine biological adhesion performance of Example 1 and Examples 4-12 Barnacle attachment percentage / % Barnacle attachment percentage / % Example 1 5 Example 9 26 Example 4 14 Example 10 20 Example 5 17 Embodiment 11 31 Example 6 9 Example 12 44 Example 7 11 Comparative Example 1 83 Example 8 16 Referring to Examples 1-3 and Comparative Example 1 and in combination with Table 4, it can be seen that the bonding strength of Examples 1-3 is significantly improved compared with Comparative Example 1, which indicates that the addition of modified waterborne polyurethane and carbon nanotubes can effectively enhance the bonding performance of weather resistant and anti-corrosion coatings.
[0049] The reason is that when epoxy resin and polyurethane are used together, the polyurethane segments and epoxy resin segments will penetrate each other, thus forming an interpenetrating polymer network structure, thereby improving the adhesion of the coating. Carbon nanotubes can form strong hydrogen bonds with the coating, enhancing the density and resistance to ion permeation of the coating, while also improving the rheology of the coating, increasing the adhesion and hardness of the coating, thereby improving the binding force of the marine anti-corrosion coating itself and effectively extending the service life of the anti-corrosion coating.
[0050] Compared with Example 1, the bonding strength of Examples 2-3 is slightly reduced, which shows that when the components of the weather-resistant anti-corrosion coating are formulated in the proportions of Example 1, the prepared weather-resistant anti-corrosion coating will have better bonding properties.
[0051] Referring to Example 1 and Comparative Example 1 and in combination with Table 5, it can be seen that the barnacle attachment ratio of Example 1 is significantly reduced compared with Comparative Example 1, which indicates that the addition of modified waterborne polyurethane and carbon nanotubes can effectively enhance the anti-marine biological adhesion performance of the weather resistant anti-corrosion coating.
[0052] Referring to Example 1 and Examples 4-5 and in combination with Table 5, it can be seen that relative to Example 1, the barnacle adhesion ratio of Examples 4-5 is slightly increased, which indicates that when the components of the modified waterborne polyurethane adopt the molar ratio of Example 1, the prepared weather-resistant and anti-corrosion coating will have better anti-marine biological adhesion performance.
[0053] Referring to Example 1 and Examples 6-7 and combining with Table 5, it can be seen that relative to Example 1, the barnacle attachment ratio of Examples 6-7 is slightly increased. This shows that when the components of the natural antifouling materials in the modified waterborne polyurethane adopt the mass proportion of Example 1, the prepared weather-resistant and anti-corrosion coating will have better anti-marine biological adhesion performance.
[0054] Referring to Example 1 and Examples 8-10 and in combination with Table 5, it can be seen that relative to Example 1, the barnacle attachment ratios of Examples 8-10 are significantly increased, which indicates that, relative to the use of extracts of Beibu Gulf gorgonian corals, seaweed eelgrass and marine streptomyces alone, the use of mixed extracts of Beibu Gulf gorgonian corals, seaweed eelgrass and marine streptomyces can inhibit marine life in multiple ways, thereby forming a synergistic effect and further reducing the attachment of marine life.
[0055] Among them, the anti-marine biological mechanism of Beibu Gulf flower coral, seaweed eel and marine streptomyces is that the extract of Beibu Gulf flower coral contains a large amount of macrolide compounds and diterpenoid compounds, and the above compounds have excellent anti-fouling activity against barnacle larvae. The seaweed eel extract contains P-cinnamic acid sulfate, which has an inhibitory effect on the attachment of marine bacteria and barnacles. The marine streptomyces extract contains butenolide, which has a degradation effect on the adhesion protein polymer formed by biological adhesion, thereby reducing the strength of biological adhesion and naturally detaching from large marine steel structures under the action of external environmental forces.
[0056] Referring to Example 1 and Example 11 and combining with Table 1, it can be seen that compared with Example 1, the barnacle attachment ratio of Example 11 is significantly improved, which shows that the addition of attapulgite can significantly improve the anti-marine biological adhesion performance of weather-resistant anti-corrosion coatings.
[0057] The reason is that the effectiveness of natural antifouling materials is relatively short, and under the scouring of seawater, the natural antifouling materials in weather-resistant anticorrosion coatings are easily precipitated and separated. Attapulgite has a large number of pore structures, which can effectively adsorb natural antifouling materials, thereby inhibiting the detachment of natural antifouling materials and indirectly improving the anti-marine biological adhesion effect of weather-resistant anticorrosion coatings.
[0058] Referring to Example 11 and Example 12 and combining with Table 1, it can be seen that compared with Example 11, the barnacle attachment ratio of Example 12 is further improved, which shows that the amphiphilic polyurethane system can also improve the anti-marine biological adhesion performance of weather-resistant anti-corrosion coatings.
[0059] The reason is that the amphiphilic polyurethane contains hydrophilic segments and hydrophobic segments, among which the hydrophilic segments are beneficial to inhibiting the formation of adhesion proteins, and the hydrophobic segments are beneficial to reducing the polarity and hydrogen bonding between the deposited bioadhesive and the matrix, thereby obtaining an excellent anti-marine biological attachment effect.
[0060] This specific embodiment is merely an explanation of the present application and is not a limitation of the present application. After reading this specification, those skilled in the art may make modifications to the present embodiment without any creative contribution as needed, but such modifications are protected by the patent law as long as they are within the scope of the claims of the present application.
Claims
1. An anti-corrosion process for large marine steel structures, characterized in that: The following steps are involved: Preliminary environmental preparation: control the surface temperature of the coated metal to 3°C higher than the dew point temperature, and the air humidity to less than 85%; First preliminary surface treatment: Use sandpaper to remove debris from the surface to be sprayed, and then use a brush to pre-coat the parts that are difficult to spray, such as the structure edge, welding holes and welding seams; One spraying: Firstly, test the spray gun, keep the spray gun vertical to the surface of the workpiece, and spray at a distance of 300-500mm; then spray with an overlap width of 50%. If dripping occurs during spraying, brush it flat immediately with a brush; the paint just sprayed should not be removed from the spray room before it is dry; Post-processing: inspect the coating surface and repair abnormal traces such as convex spots, overspray, roughness, pinholes, depressions, and coating leaks; Second treatment: Use sandpaper to remove pollutants on the surface of the first coating, and then perform gun test, spraying and repair operations; In the first spraying and second treatment, weather-resistant anti-corrosion coating is used for spraying, and the weather-resistant anti-corrosion coating includes the following raw materials in parts by weight: 90-110 parts of water-based epoxy resin emulsion, 10-16 parts of modified water-based polyurethane, 5-10 parts of water-based epoxy curing agent, 10-20 parts of carbon nanotubes, 3-8 parts of film-forming aid, 0.2-0.8 parts of defoaming agent, 0.3-0.9 parts of wetting agent, 0.6-1.2 parts of dispersant, 0.6-1.2 parts of leveling agent and 10-16 parts of water.
2. The anti-corrosion process for large marine steel structures according to claim 1 is characterized in that: In the first post-treatment and the second treatment, the repair operation is: sandpaper is used to grind within 50mm around the abnormal area to make the coating surface rough, and then local spray repair is performed when the single abnormal trace area is not larger than 1 square foot and the sum of the damaged area does not exceed 10% of the total area, otherwise the whole borax is applied and re-painted.
3. The anti-corrosion process for large marine steel structures according to claim 1, characterized in that: For paint damage that exposes the base material, the repair operation is as follows: clean the damaged area to remove contaminants, then use rubber to protect the intact paint surface and tie it up with wire or tape, then apply borax to the damaged area to SA 21 / 2, then grind the paint in the junction area to remove fine cracks; Then, sand the edges of the damaged area and the intact area to create an overlapping slope. The original coating in the overlapping area should be sanded to reveal a fresh coating surface. Finally, clean the surface and apply the paint.
4. The anti-corrosion process for large marine steel structures according to claim 1, characterized in that: The modified waterborne polyurethane contains natural antifouling materials, which are extracts of one or more of Beibu Gulf flower corals, seaweed giant algae and marine streptomyces.
5. The anti-corrosion process for large marine steel structures according to claim 4, characterized in that: The natural antifouling material is a mixed extract of Beibu Gulf gorgonian coral, seaweed giant kelp and marine streptomyces, and the mass ratio of Beibu Gulf gorgonian coral, seaweed giant kelp and marine streptomyces is (3-5): (1-3): (2-4).
6. The anti-corrosion process for large marine steel structures according to claim 4, characterized in that: The modified waterborne polyurethane contains attapulgite, and the natural antifouling material is loaded on the attapulgite.
7. The anti-corrosion process for large marine steel structures according to claim 6, characterized in that: The modified waterborne polyurethane comprises the following raw materials in molar parts: 1-3 parts of 1-thioglycerol, 5-10 parts of butyl acrylate, 5-10 parts of N-vinyl pyrrolidone, 0.1-0.2 parts of 2,2-azobisisobutyronitrile, 10-20 parts of isophorone diisocyanate, 2-8 parts of double-terminal hydroxypropyl silicone oil, 0.5-1.5 parts of polytetrahydrofuran, 0.4-0.8 parts of dibutyltin dilaurate, 6-10 parts of 1,4-butanediol, 1-3 parts of triethanolamine, 3-5 parts of attapulgite and 2-4 parts of natural antifouling materials.
8. The anti-corrosion process for large marine steel structures according to claim 7, characterized in that: The preparation method of the modified waterborne polyurethane comprises the following steps: S1, dissolving 1-thioglycerol, butyl acrylate, N-vinyl pyrrolidone and 2,2-azobisisobutyronitrile in tetrahydrofuran, and then reacting at 70° C. for 12 h under a nitrogen atmosphere, then removing the solvent, and precipitating with petroleum ether, and finally drying the precipitate to obtain a hydrophilic polymer; S2, dissolving isophorone diisocyanate, double-terminated hydroxypropyl silicone oil, polytetrahydrofuran and dibutyltin dilaurate in tetrahydrofuran, and then reacting at 70°C for 3h, then adding 1,4-butanediol and a hydrophilic polymer, heating to 80°C for 3h, and then adding triethanolamine to continue the reaction for 0.5h, and finally obtaining an amphiphilic polyurethane; S3, soaking the attapulgite in natural antifouling materials, then drying it naturally, and then mixing it with amphiphilic polyurethane to obtain modified waterborne polyurethane.
9. The anti-corrosion process for large marine steel structures according to claim 1, characterized in that: The preparation method of the weather-resistant anticorrosive coating comprises the following steps: Step 1: Mixing the waterborne epoxy resin emulsion and the modified waterborne polyurethane, and then sequentially adding a defoamer, a wetting agent, a dispersant, a leveling agent and water to obtain a coating base material; Step 2: adding carbon nanotubes to the coating base material and continuing to mix to obtain a weather-resistant and anti-corrosion coating body; Step 3: Mix the water-based epoxy curing agent with the weather-resistant anti-corrosion coating to finally obtain the weather-resistant anti-corrosion coating.